PELATIHAN PUBLIC SPEAKING UNTUK MENINGKATKAN KEMAMPUAN BERBICARA MAHASISWA DAN MASYARAKAT PADA KEGIATAN BAKTI SOSIAL UPMI DI DESA SINGAPADU KALER SUKAWATI - Putu Dessy Fridayanthi; Gusti Ayu Made Puspawati; Ida Ayu Agung Ekasriadi (Jurnal Pengabdian Kepada Masyarakat Widya Mahadi, 2025)
This community service program aimed to improve the public speaking skills of students and community members through a training program conducted as part of the Universitas PGRI Mahadewa Indonesia (UPMI) Social Service Program in Singapadu Kaler Village, Sukawati District, Gianyar Regency. This program was motivated by the low level of self-confidence and public communication skills among students and the local community in social and academic activities. The implementation method applied a participatory empowerment approach consisting of socialization, training, practice and mentoring, and evaluation stages. The training was conducted through interactive lectures, simulations, direct practice, and continuous feedback. Evaluation was carried out using pre-test and post-test, performance observation, and self-confidence questionnaires. The results showed a significant improvement in participants’ abilities in terms of content delivery, speaking fluency, use of body language, and self-confidence when speaking in public. Participants also demonstrated better skills in structuring messages systematically and delivering ideas more effectively. This program had a positive impact on enhancing the communication competence of both students and community members as a provision for academic activities, organizational involvement, and social participation. Therefore, public speaking training is proven to be an effective effort to strengthen soft skills and empower human resources in Singapadu Kaler Village.